RANCANG BANGUN APLIKASI E-COMMERCE BERBASIS WEB PADA TOKO ZIFA BEAUTY - Armilia, Puti Selvi; Sasa Ani Arnomo (LPPM Universitas Putera Batam, 2024)
Zifa Beauty is a business that offers a variety of skincare products and fragrances. Data processing in shop management is still done by hand. The aim of this research is to create a web-based e-commerce application for Zifa Beauty Store via design and development. The author employs the V-Model approach, which enables users to assess the system and documentation acceptability at the conclusion of the development phase. The outcomes showed that with an automated sales system, stores can easily track transactions made by specific customers. This information can help in recognizing customer preferences and buying habits, so that stores can provide more personalized and interesting services for customers, Structured transaction data can be used to conduct in-depth sales analysis. Store owners can view sales trends over time, identify best-selling products, and identify new business opportunities. Sales data recorded in the database allows stores to forecast future stock needs. Based on sales trends, stores can project the level of demand for a particular product and organize purchase orders more precisely.